(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Age-related macular degeneration (AMD) leads to partial or complete loss of central vision, causing disability of patients. The current problem explains completely the search for new methods of influence on the visual analyzer in patients with AMD. The рurpose. To study the changes in visual acuity in patients with the dry form of AMD after two courses of low-energy light therapy and medication. Material and methods. Study Group was made up of 115 patients (187 eyes), which took two courses of low energy light therapy (LELT) in combination with two courses of medication in the hospital for 10 days each. Control Group consisted of 95 patients (163 eyes), which passed only two courses of medication in the hospital for 10 days each. Time points of follow up were before treatment (baseline), after treatment, 1, 3, and 6 months after the first course of treatment. Afterwards, the second treatment course was performed with the same time points. Visual acuity testing was performed using ETDRS tables (number of characters). Depending on the visual acuity (VA), Study Group was divided as follows: Subgroup I, 54 eyes ? 47 fig.; Subgroup II, 133 eyes > 47 fig. Control Group: Subgroup I, 47 eyes ? 47 fig.; Subgroup II, 116 eyes > 47 fig. Results and their discussion. After completing two courses of treatment,VA rate improvement was by 21.6% better in Study Subgroup I patients than in Control Subgroup I ones, i.e. (22 eyes (40.7%) vs. 9 eyes (19.1%), respectively; VA rate stabilization was noted in 6 eyes (11.1% cases) of Study Subgroup I patients. Overall, treatment was more successful by 32.7% in Study Group as compared with Control Group, i.e. 28 eyes (51.8%) vs. 9 eyes (19.1%), respectively. Decrement in VA rates was less by 32.8% in Study Group than in Control Group, i.e. 26 eyes (48.1 %) vs. 38 eyes (80.9 %), respectively. After completing two courses of treatment in patients of Study and Control Subgroups II, VA improvement rates were higher by 79.8% in Study Group patients than in those of Control Group, i.e. 113 eyes (85.0%) vs. 6 eyes (5.2%), respectively; VA stabilization rates were higher by 4.6% in Control Group patients than in those of Study Group, i.e. 15 eyes (12.9%) vs. 11 eyes (8.3%), respectively. Overall, treatment success was higher by 75.2% in Study Group than in Control one, i.e. 124 eyes (93.3%) vs. 21 (18.1%), respectively. Conclusions. 1.It was found that AMD patients with low vision had stabilization of VA rates (pre-treatment (28.6±1.0) figures, post-treatment (28.7±1.1) figures, р=0.496) after two joint courses of low-energy light therapy and medication; meanwhile, patients receiving medication only therapy had significant decrement in visual acuity from (29.3±1.0) to (26.2±1.2) figures (р=0.000). 2.It was revealed that, after two joint courses of low-energy light therapy and medication, AMD patients with high VA rates had significant increase of VA rates from (71.4±0.8) figures at baseline to (76.6±0.9) figures at 12 months, (р=0.000); while VA rates decreased from (69.5±0.9) to (66.3±0.9) (р=0.000), respectively, in patients receiving medication only therapy. 3.It was noted that treatment of AMG patients both with poor and high VA rates who underwent two joint courses of low-energy light therapy and medication was more successful than in those who received two courses of medication only therapy. The difference between them was 32.7% (14.0 ? 48.15. р=0.001) for poor VA rates and 75.2% (65.4 ? 81.9, р<0.000) for high VA rates.4.Success of low-energy light therapy in combination with medication course in AMD patients depends on baseline VA rates: the higher visual acuity is, the more successful is the treatment.